2016
DOI: 10.1016/j.molcel.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Nbs1 Converts the Human Mre11/Rad50 Nuclease Complex into an Endo/Exonuclease Machine Specific for Protein-DNA Adducts

Abstract: The human Mre11/Rad50/Nbs1 (hMRN) complex is critical for the sensing, processing, and signaling of DNA double-strand breaks. The nuclease activity of Mre11 is essential for mammalian development and cell viability, although the regulation and substrate specificity of Mre11 have been difficult to define. Here we show that hMRN catalyzes sequential endonucleolytic and exonucleolytic activities on both 5' and 3' strands of DNA ends containing protein adducts, and that Nbs1, ATP, and adducts are essential for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
164
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 61 publications
18
164
0
Order By: Relevance
“…1B, lanes 4 and 5); thus, we conclude that the processing is done by the catalytic activity of Mre11. We have previously observed that ATP binding by Rad50 promotes Nbs1-dependent endonucleolytic cutting by Mre11 (8,19). Here we find that ATP is essential and the nonhydrolyzable AMP-PNP analog does not substitute for ATP in promoting MRN nuclease activity in the presence of DNA-PK (Fig.…”
Section: Main Textmentioning
confidence: 49%
See 4 more Smart Citations
“…1B, lanes 4 and 5); thus, we conclude that the processing is done by the catalytic activity of Mre11. We have previously observed that ATP binding by Rad50 promotes Nbs1-dependent endonucleolytic cutting by Mre11 (8,19). Here we find that ATP is essential and the nonhydrolyzable AMP-PNP analog does not substitute for ATP in promoting MRN nuclease activity in the presence of DNA-PK (Fig.…”
Section: Main Textmentioning
confidence: 49%
“…Our previous studies of MRN and Ku dynamics on DNA ends using the DNA curtains system and ensemble assays showed MRN cleavage of Ku alone, but this reaction required manganese ions (8,12). Other studies also recently demonstrated yeast Mre11/Rad50/Xrs2(MRX) cleavage of various protein blocks including yeast Ku, which was also manganese-dependent in vitro (10, 11).…”
Section: Cc-by-nc-ndmentioning
confidence: 95%
See 3 more Smart Citations